Counseling Guidance and Value Education to Prevent Radicalism and Terrorism - Dewi Sadiah (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2019)
This research aims to reveal several solutions for counseling and value education guidance programs that are made into policies by lecturers in the prevention of terrorism and radicalism. The method used in this study is a comparative method with a qualitative approach that is natural. The results achieved by lecturers through counseling and education on values against the prevention of radicalism and terrorism can be seen from UIN Jakarta, which collaborates with lecturers and students to understand the meaning of the Koran and hadiths that are not radical and encourage Muslims to behave better and be peaceful. UIN Yogyakarta conducts coaching, awareness, and banning veiled female students in the campus area. Meanwhile, UIN Malang prevents radicalism and terrorism on campus, rejects all forms of right and left extremism, and maintains unity and integrity.Penelitian ini bertujuan untuk mengungkapkan beberapa solusi program bimbingan konseling dan pendidikan nilai yang dijadikan kebijakan oleh dosen dalam pencegahan terorisme dan radikalisme. Metode yang digunakan dalam penelitian ini adalah metode komperatif dengan pendekatan kualitatif yang bersifat alami. Hasil yang dicapai oleh dosen melalui konseling dan pendidikan nilai terhadap pencegahan radikalisme dan terorisme dapat dilihat dari UIN Jakarta yang melakukan kerjasama dosen dan mahasiswa untuk memahami makna al-Quran dan hadis tidak bersifat radikal dan menganjurkan umat Islam untuk bersikap lebih baik dan tasamuh. UIN Yogyakarta melakukan pembinaan, penyadaran, pelarangan mahasiswi bercadar di area kampus. Sementara itu, UIN Malang mencegah radikalisme dan terorisme di kampus, menolak segala bentuk ekstrimisme kanan dan kiri, serta menjaga persatuan dan kesatuan.